MODEL ISOMORFIS DALAM PERSPEKTIF AL-QUR’AN PADA PENDIDIKAN ANAK USIA DINI - Ahmad Masruri (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2022)
This study proves that to improve intellectual intelligence, emotional intelligence and spiritual intelligence of early childhood, is the isomorphic model in the perspective of the Qur'an, which includes three main educational matters, namely: aqidah (tawhid), morals, worship. This research is a qualitative research to reveal the social situation that occurred in PAUD. The data collection is done by collecting sources and from primary and secondary data. In analyzing the data that has been collected the author uses data analysis (content analysis). A concept used by commentators in explaining the content of the verses of the Qur'an from various aspects by paying attention to the verses of the Qur'an as stated in the manuscripts. It starts by mentioning the verses to be interpreted, explaining the meaning of the lafadz contained therein. Then the interpreted verses are described and analyzed clearly, so that conclusions can be drawn.